Impact of desilting by excavation on water quality in a water reservoir in the municipality of Fernandópolis, SP - Ramos, Elise Baroni; Mansano, Cleber Fernando Menegasso; Américo-Pinheiro, Juliana Heloisa Pinê; Vanzela, Luiz Sergio (Periódico Eletrônico Fórum Ambiental da Alta Paulista, 2023)
Desilting is an important job in restoring water reservoirs, but it disturbs the environment and has a potential impact on water resources. The objective of this work was to evaluate the impact of the desilting operation by excavation on the water quality of Córrego da Aldeia, Fernandópolis/SP. The experimental design was completely randomized in a 2x3x4 factorial scheme, in which the main factors were constituted by the runoff periods (with and without runoff), the secondary by the excavation periods (before, during and after excavation) and the tertiary by the points of monitoring (upstream points E1, E2 and E3 and downstream point S, in relation to the reservoir). Samples and analyzes of the physical, chemical and biological variables of the water were collected between July 2020 and March 2022. After that, analysis of variance of the isolated factors and their interaction was performed, followed by a mean comparison test. Through the results, it was observed that the work impacted the water quality in the concentration of ammonium and ammonia in 154.1% and 151.9%, respectively. The other qualitative water variables evaluated (water temperature, hydrogenionic potential, dissolved oxygen, electrical conductivity, total coliforms and Escherichia coli) were impacted due to climate and/or use and occupation of the soil around the collection points.